2021
DOI: 10.24095/hpcdp.41.6.03
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators encountered by family physicians prescribing opioids for chronic non-cancer pain: a qualitative study

Abstract: Introduction Harms caused by prescription opioid analgesics (POAs) have been identified as a major international public health concern. Recent statistics show rising numbers of opioid-related deaths across Canada. However, Canadian family physicians appear to have inadequate resources to safely and effectively prescribe opioid analgesics to treat chronic non-cancer pain (CNCP). Methods We completed a qualitative study of the barriers and facilitators to safe and effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“… 44 GPs reported reasons for not referring to specialised pain centres or private specialists included long waitlists, lack of affordability and likelihood that these referrals would end in opioid prescription anyhow as. 42 44 GPs interviewed by Desveaux et al 38 wanted a more interdisciplinary approach for chronic pain management. GPs reported that an impaired kidney function and contraindications made other pharmacological options limited.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 44 GPs reported reasons for not referring to specialised pain centres or private specialists included long waitlists, lack of affordability and likelihood that these referrals would end in opioid prescription anyhow as. 42 44 GPs interviewed by Desveaux et al 38 wanted a more interdisciplinary approach for chronic pain management. GPs reported that an impaired kidney function and contraindications made other pharmacological options limited.…”
Section: Resultsmentioning
confidence: 99%
“…34–47 The sample size ranged from 5 to 27 GPs. Five studies included solely GPs,37 38 41 42 44 and remaining studies also interviewed other primary care providers (PCP). In the USA, the term PCP is used for physicians providing primary care and consists of family doctors, internists, paediatrics, geriatrics, gynaecologists and nurse practitioners and physician assistants 48.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations